Nutritional factors associated with anaemia in pregnant women in Tulang Bawang Lampung - Nisrina Fadhilaturrabani; Dessy Hermawan; Nurul Aryastuti; Fitri Ekasari Siregar; Nova Muhani (Malahayati International Journal of Nursing and Health Science, 2022)
Background: Anemia is the biggest health problem in the world, especially for women who are pregnant, because it can cause fatigue and decreased work productivity. Knowledge is a factor that encourages pregnant women to avoid anemia. If pregnant women know the causes of anemia, the consequences of anemia, and how to prevent it, pregnant women will avoid pregnancy anemia.Purpose: To find out the determinants of the incidence of Anemia in Pregnant Women at the Non-Inpatient of candra mukti health center and Inpatient health center at capable ponet Tulang Bawang Barat working area in 2022.Method: Quantitative analytic research with cross sectional design. The sampling technique used proportional stratified random sampling, and 171 people met the inclusion criteria. Data analysis used the Chi Square test and multivariate analysis used multiple logistic regression.Results: It is known that the distribution of the majority of anemic mothers (59.1 percent). have less knowledge (53.8 percent). have a positive attitude (52.6 percent). obediently consuming Fe tablets (58.5 percent). 1 glass (66.1 percent) of iron absorption inhibiting drinks (tea, coffee, milk). get good family support (59.6 percent). received the support of good health workers (71.9 percent).Conclusion: There is a significant relationship between knowledge, attitudes, adherence to iron consumption, drinking iron absorption inhibitors (tea, coffee and milk), family support and support from health workers with the incidence of anemia in pregnant women with a p-value of < 0.05. Fe consumption is the dominant factor in the incidence of anemia in pregnant women (p-value = 0.002).